Improving phosphorus uptake and wheat productivity by phosphoric acid application in alkaline calcareous soils. (4th January 2016) - Akhtar, Muhammad; Yaqub, Muhammad; Naeem, Asif; Ashraf, Muhammad; Hernandez, Vicente Espinosa
Abstract: BACKGROUND: Low phosphorus (P) efficiency from existing granular fertilisers necessitates searching for efficient alternatives to improve wheat productivity in calcareous soil. RESULTS: Multi‐location trials have shown that phosphoric acid (PA) produced 16% higher wheat grain over commercial P fertilisers, i.e. diammonium phosphate (DAP) and triple superphosphate (TSP). Methods of P application significantly influenced grain yield and the efficiency of methods was observed in the order: PA placement below seed > PA, DAP or TSP fertigation > DAP or TSP broadcast. The sub‐surface application of PA produced highest grain yields (mean of all rates), i.e. 4669, 4158 and 3910 kg ha −1 in Bagh, Bhalwal and Shahpur soil series, respectively. Phosphoric acid at 66 kg P2 O5 ha −1 was found more effective in increasing gain yield over that of control. Trend in grain P uptake was found similar to that observed for grain yield. Maximum P uptake by grain was recorded at the highest P rate and the lowest at zero P. The significant increase in P uptake with P rates was generally related to the increase in yield rather than its concentration in grain. Phosphorus agronomic efficiency (PAE) and phosphorus recovery efficiency (PRE) were found higher at lower P rate (44 kg P2 O5 ha −1 ) and decreased with P application. However, PA applied by the either method resulted in higher PAE and PRE compared to DAP and TSP. CONCLUSION: Phosphoric acid is suggested as an efficient alternative to commercial granular P fertilisers for wheat production in alkaline calcareous soils. © 2015 Society of Chemical Industry